الاحتياجات التكوينية لدى مستشاري التوجيه من وجهة نظرهم - قلاعة, حنان (كلية العلوم الاجتماعية, 2025)
هدفت هذه الدراسة إلى التعرف على الحاجات التكوينية لدى مستشاري التوجيه من وجهة نظرهم وكذلك التعرف على درجة الاحتياج لديهم والفروق بينهم التي تعزى لكل من المتغيرات التالية ( الجنس ، التخصص الأكاديمي ، والخبرة المهنية ) .حيث تم تطبيق أدوات الدراسة والمتمثلة في استبيان والذي طبق على عينة قوامها (75) مستشارا (ة) تم اختيارهم بطريقة قصدية بمدينة مستغانم ،سنة (2024-2025) واستخدمت الطالبة الباحثة المنهج الوصفي الذي يتناسب مع طبيعة الدراسة حيث أظهرت نتائج الدراسة باستخدام برنامج الحزمة الإحصائية للعلوم الاجتماعية إلى النتائج التالية :« spss v20 » _ توجد حاجات تكوينية مرتفعة في بعد الارشاد والتكفل والمرافقة لدلى مستشاري التوجيه من وجهة نظرهم. _لا توجد فروق ذات دلالة احصائية في تقدير الحاجات التكوينية لدى مستشاري التوجيه تعزى لمتغير الجنس. _لا توجد فروق ذات دلالة احصائية في الحاجات التكوينية لدى مستشاري التوجيه تعزى لمتغير التخصص الأكاديمي. _توجد فروق ذات دلالة احصائية في الحاجات التكوينية لدى مستشاري التوجيه تعزى لمتغير الخبرة المهنية لصالح أقل من خمس سنوات. This study aimed to identify the training needs of guidance counselors from their own perspectives, as well as to determine the level of these needs and the differences between them based on the following variables: gender, academic specialization, and professional experience. The study tools consisted of a questionnaire administered to a purposive sample of 75 guidance counselors in the city of Mostaganem during the academic year 2024–2025. The researcher adopted the descriptive method, which suits the nature of the study. The results, obtained using the Statistical Package for the Social Sciences (SPSS), revealed the following: There are high training needs in the areas of counseling, support, and guidance from the perspective of guidance counselors. There are no statistically significant differences in the assessment of training needs among guidance counselors based on the gender variable. There are no statistically significant differences in the training needs of guidance counselors based on the academic specialization variable. There are statistically significant differences in the training needs of guidance counselors based on the variable of professional experience, in favor of those with less than five years of experience.
دراسة ميدانية بمركز التوجيه والإرشاد المدرسي والمهني مستغانم
Keywords: الاحتياجات التكوينية ؛ مستشار التوجيه